Synergistic selection how cooperation has shaped evolution and the rise of humankind - Corning, Peter A. 1935- (World Scientific Publishing Co. Pte Ltd., 2018)
"Nothing about the evolution of biological complexity makes sense except in the light of synergy." Peter Corning's new book is being hailed as a major contribution to what is perhaps the greatest shift in our understanding of evolution since The Origin of Species. It's a tour de force that takes us on a synergy-guided tour of the history of life. As Corning puts it, "life on Earth has been a synergistic phenomenon from the get go." Corning also shows how synergy has been a key to human evolution, including the rise of complex modern societies. "Cooperation may have been the vehicle, but synergy was the driver." As we now face a tipping point and another major transition in evolution, Corning offers us a synergy-based road-map to the future. "One of the great take-home lessons from the epic of evolution is that cooperation produces synergy, and synergy is the way forward. The arc of evolution bends toward synergy."--